Restoring Land and Growing Renewable Energy: Opportunities, Challenges, and the Future Steps - Maimunah, S.; Rahman, S. A.; Baral, H. (JIPI, Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Primary energy demand in Indonesia has rapidly increased, i.e., 43.33% between 2005 and 2016, while domestic energy supply failed to fulfill these needs leading to the reliance on the energy import. Meanwhile, a vast area of degraded land in Indonesia also created an opportunity for biofuel production, fulfilling energy demand, as well as restoring the land with environmental and socio-economic benefits. This paper provides an overview of identified potential and challenges associated with biofuel production from degraded land in Indonesia. Our preliminary findings highlighted that some biofuel species in Indonesia are suitable to grow in degraded land and potentially restore the land that may not be suitable for current agricultural production and/or reforestation. The initial finding also shows that culturally familiar species and stable markets are favorable terms of biofuel-species selection for the landowners. Supportive agricultural-extension services such as knowledge and technology for honey production can provide an added value in this concept, in addition to social (e.g., strengthening social solidarity and employment opportunities) and environmental (e.g., carbon storage, soil moisture, erosion control, and biodiversity) benefits. Meanwhile, to create this overall initiative to be successful, a supportive measure from the policymakers is needed. Further research on the capacity of biofuel species to restore degraded lands in different biophysical profiles. Analysis of biofuel production feedstocks and potential co-benefits viable business models, and the stable market is necessary to maximize benefit from biofuel production and to restore the degraded lands in Indonesia.